Protective effect of nigella sativa and thymoquinone on relative liver weight increase caused by aflatoxin in broilers - Mehmet Burak Ateş; Mustafa Ortatatlı (Eurasian Journal of Veterinary Sciences)
Aim: It is aimed to determine the preventive effect of black seed (Nigella sativa L; NS) and its pharmaceutically active substance volatile fatty acid thymoquinone on relative liver weight increase in broiler in aflatoxicosis.. Materials and Methods: One hundred twenty 1-d-old broiler chicks were used and divided into 6 equal groups and fed for 28 days. Animals were received feed with 2 mg/kg total aflatoxin (AF; AFB1, AFB2, AFG1 and AFG2), 5% black seed (NS) and 300 mg/kg thymoquinone (TQ), according to the groups; Control, AF, NS, TQ, AF+NS and AF+TQ. At the end of the experiment, euthanasia was performed by decapitation after determination of the live weight of ten broiler chickens in all groups, and systemic necropsies were performed. The liver, the main target organ for AF, was removed and weighed to determine relative organ weight. The relative liver weights were calculated as % (liver weight x 100 / live body weight). Results: Aflatotoxin application significantly increased the relative weight of the liver (P<0,01). While the difference was not significant in the TQ group compared to the control group, a significant increase in liver weight was found in the NS group. Addition of TQ to feeds with AF significantly reduced the relative liver weight values to normal. NS effect was found more partial compared to TQ. Conclusion: In conclusion, it was thought that TQ and NS prevented the relative liver weight increase, an important biomarker for aflatoxicosis, by probably ameliorating lipid metabolism and transport which is impaired by the toxic effect of AF.